ADDENDUM: About a New Fusion Reactor Scheme. (3rd October 2019) - Mazzucato, E.
Abstract: A crucial problem of any steady-state fusion reactor is removal of the plasma exhaust. In this addendum to the paper "About a New Fusion Reactor Scheme" [Fusion Sci. Technol., Vol. 75, p. 197 (2019)], we analyze the possibility of achieving this goal in the fusion reactor scheme by using a model C stellarator type of divertor.